PENERAPAN PENGALAMAN RUANG (USER EXPERIENCE) SEBAGAI MEDIA BARU DALAM PERANCANGAN LIVING MUSEUM DI PASAR IKAN, JAKARTA UTARA - Prisilla Noviani Soehardinata; Suwardana Winata (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The Pasar Ikan area, as one of the starting points for the development of Jakarta in the Batavia era, is one of the biggest fish markets of its time. As years passed, Pasar Ikan degraded and changed its function into a slum settlement, resulting in a loss in its image as a historical and maritime area. This situation then becomes a trigger to restore the image of the Pasar Ikan area, by considering current conditions and the need in providing education for the community. Museums are one of many ways to educate the public about the history of Pasar Ikan. However, it was found that the number of public visits to museums is still very low, especially among the millennial generation. Hence, a new media, that is relevant to current development, is required to convey information in the museum. The methods used are Translating History into User Experience, Everydayness based on a participatory approach and narrative tactics, and 4 Space Plot Strategies. In conclusion, the user experience in the Living Museum is built through: 1. Translating History into Space Experience which results in Past, Present, and Future zoning; 2. Daily analysis that produces aspects of the five senses of the present and the past; 3. 4 Space Plot Strategies that produce Zoning, Zone Section & Events, 5 Sense Experiences (both architecturally in the form of dioramas and non-architecturally by using actors), and Spatial Configuration. Keywords: adaptive-reuse; everydayness; living museum; user experience